Análisis del impacto en la precisión del cálculo de métricas de variabilidad glucémica en registros de glucosa que presentan pérdida de datos (2023)
The international endocrine association has a consensus of metrics, which are used to assess glycemic variability from continuous glucose monitoring sensor measurements. Glucose monitoring records sample every 5 minutes and are useful for detecting episodes of hypo/hyperglycemia in patients with diabetes. Communication failures, device misuse and other reasons lead to data loss affecting the calculation of metrics.